Jernang rattan (Daemonorops draco) management by Anak Dalam Tribe in Jebak Village, Batanghari, Jambi Province - IIK SRI SULASMI; NISYAWATI NISYAWATI; YOHANES PURWANTO; SITI FATIMAH (Biodiversitas Journal of Biological Diversity, 2012)
Sulasmi IS, Fatimah S, Nisyawati. 2012. Jernang rattan (Daemonorops draco) management by Anak Dalam Tribe in Jebak Batanghari, Jambi Province. Biodiversitas 13: 151-160. Management of Jernang Rattan (Daemonorops draco Willd.) in Jebak Forest, Batanghari, Jambi is not well documented. It is noted that fruit of D. draco is the best income source for Anak Dalam Jambi people since 1624. They harvest fruit of D. draco as much as they need. The Jebak forest is an open access, so all the people of Anak Dalam Jambi Tribe have the same right and responsibility on the forest. However, almost 60% of Jebak Forest area has been degraded because of illegal conversion into oil palm plantation. This is the reason why people of Suku Anak Dalam, try to cultivate D. draco by growing 40 clumpsof this species in their rubber plantation. The aim of their activity is to conserve D. draco at their forest. Based on the recent situation, research study of jernang rattan management in Jebak Forest was conducted. The research method was semi structural interview. All data were analyzed descriptively. The results showed that the management and cultivation of D. draco in Jebak Forest was very difficult because the availability of seeds was not sufficient for root stocks.